Seroprevalence of antibodies against hepatitis C virus in Female sex workers patients from the sexually transmitted Infections Reference Center in Iquitos, Peru - Guerra Amaya, O. (2024)
Introducction: the principal described risk factors to contract the hepatitis C virus (HCV) are blood transfusion antecedents and intravenous drug use; sexual transmission risk is controversial. In Peru there exist few studies whose female sex worker (FSW) HCV prevalence oscillates between 0-1%. The present study is based in Iquitos, a Peruvian jungle city with high sexual commerce and HIV/AIDS prevalence. Objetive: determine the HCV serological prevalence in Iquitos FSWs attending the STI/ HIV specialist center (CERITSS) and identify associated risk factors. Material and methods: cross-sectional study in FSWs who attended periodic San Juan CERITSS examinations from May 2003 to January 2004. Epidemical questionnaires where used to evaluate the risk factors. To determine HCV antibodies presence, the immunoassay enzyme (EIA) positive results were confirmed by the recombinant immunoblot assay (RIBA) test. Results: 4/200 FSWs enrolled in the study were EIA test positive; all had confirmed positive RIBA results, representing 2%(95%IC 0,06%-3,94%) prevalence. the 4 FSWs referred to be were born in Iquitos, to having been a sex worker for >five years and stated condom use was <50%. Three to having had >9 sexual clients daily; to heavy alcohol consumption and to frequent anal sex . None declared intravenous drug use; having had tattoos and blood transfusions. Only one of 4 HCV positives had syphilis serology and none had HIV infections. 1/200 was diagnosed with HIV. Conclusion: the antibody against HCV seroprevalence in Iquitos FSWs is greater than reported in similar populations or the general population of other Peruvian cities. This population was characterized by having high risk sexual behavior and no blood transfusion antecedent nor intravenous drug user